WEB BASED ONLINE MUSIC CLASS DESIGN (Ganesha Dheva Music) - Cahyo Aji Pangestu; Dimas Fanny Hebrasianto Permadi (JOSAR (Journal of Students Academic Research), 2021)
Technology is always used in various aspects of life, especially in the arts. Ganesha Dheva Musik is a course that always tries to keep up with technological developments to improve quality. However, there are still problems with this course such as offline learning. Based on these problems, a hybrid learning website is needed that can help solve these problems. The results obtained from this study are a website that can be used for all students at Ganesha Dheva Musik. The hybrid learning website can help solve learning problems offline to online and make assignments in each material.